Express with caution: Epitope tags and cDNA variants effects on hERG channel trafficking, half‐life and function. (23rd June 2017) - Osterbur Badhey, Marika L.; Bertalovitz, Alexander C.; McDonald, Thomas V.
Abstract: Introduction: Genetic mutations in KCNH2, which encodes hERG, the alpha subunit of the potassium channel responsible for the IKr current, cause long QT syndrome (LQTS), an inherited cardiac arrhythmia disorder. Electrophysiology techniques are used to correlate genotype with molecular phenotype to determine which mutations identified in patients diagnosed with LQTS are disease causing, and which are benign. These investigations are usually done using heterologous expression in cell lines, and often, epitope fusion tags are used to enable isolation and identification of the protein of interest. Methods and results: Here, we demonstrate through electrophysiology techniques and immunohistochemistry, that both N‐terminal and C‐terminal myc fusion tags may perturb hERG protein channel expression and kinetics of the IKr current. We also characterize the impact of 2 previously reported inadvertent cDNA variants on hERG channel expression and half‐life. Conclusion: Our results underscore the importance of careful characterization of the impact of epitope fusion tags and of confirming complete sequence accuracy prior to genotype‐phenotype studies for ion channel proteins such as hERG.